User interface design for open and closed loop control system / Mohd Idzham Abdul Wahab - Abdul Wahab, Mohd Idzham (2017)
The purpose of this paper is to develop user interface design for open and closed loop control system. The development of the system is accomplished via G-programming language potentialities of LabVIEW™ version 2011 running on ACER Intel Core™ i5-6200U 2.3GHz with Turbo Boost up to 2.8GHZ, 8GB DDR4 computer with Window10 Home operating system. This system is designed as a teaching and learning aid for the air pressure control trainer model SOLTEQ SE121 which installed at the Process Control Laboratory, Faculty of Electrical Engineering, UiTM Shah Alam. The system developed will help students to understand more about open and closed loop control system.